One threat, different answers: the impact of COVID-19 pandemic on cornea donation and donor selection across Europe. Issue 3 (26th November 2020) - Thuret, Gilles; Courrier, Emilie; Poinard, Sylvain; Gain, Philippe; Baud'Huin, Marc; Martinache, Isabelle; Cursiefen, Claus; Maier, Philip; Hjortdal, Jesper; Sanchez Ibanez, Jacinto; Ponzin, Diego; Ferrari, Stefano; et al.
Abstract : Objectives: To assess to which extent the COVID-19 pandemic affected corneal transplantation by virtue of donor selection algorithms in different European countries. Design: Survey. Setting: 110 eye banks in 26 European countries. Participants: 64 eye banks covering 95% of European corneal transplantation activity. Interventions: A questionnaire listing the number of corneas procured and distributed from February to May 2018–2020 was circulated to eye banks. Main outcome measures: The primary outcome was the number of corneal procurements. Additional outcomes were national algorithms for donor selection, classified according to their stringency (donors with COVID-19 history, suspected for COVID-19, asymptomatic, PCR testing) and the pandemic severity in each country. We calculated Spearman's correlation coefficient to determine, two by two, the relationship between the 3-month decline in eye banking activity (procurement), the stringency of donor selection algorithm and the grading of pandemic severity (cases and deaths). A partial correlation was run to determine the relationship between decline and stringency while controlling for pandemic severity. Results: Procurements decreased by 38%, 68% and 41%, respectively, in March, April and May 2020 compared with the mean of the previous 2 years, while grafts decreased, respectively, by 28%, 68% and 56% corresponding to 3866 untreated patients in 3 months. Significant disparities between countries and the decrease in activity correlated with stringency in donor selection independent of pandemic severity. Conclusions: Our data demonstrate significant differences between countries regarding donor screening algorithms based on precautionary principles and, consequently, a decrease in the donor pool, already constrained by a long list of contraindications. Fundamental studies are needed to determine the risk of SARS-CoV-2 transmission by corneal transplantation and guide evidence-based recommendations for donor selection to justify their substantial medical and economic impact.